An industrialized diet as a determinant of methylation in the 1F region of the NR3C1 gene promoter - Vieira, Tamires dos Santos; Freitas, Flávia Vitorino; Silva Neto, Luiz Cláudio Barreto; Borçoi, Aline Ribeiro; Mendes, Suzanny Oliveira; Olinda, Amanda Sgrancio; Moreno, Ivana Alece Arantes; Quaioto, Bárbara Risse; de Souza, Marcele Lorentz Mattos; Barbosa, Wagner Miranda; Arpini, Juliana Krüger; Sorroche, Bruna Pereira; et al. (Frontiers in Nutrition, 2024)
Background: A diet's composition can modify gene expression, favoring the development of chronic diseases through epigenetic mechanisms.Objective: Our study aimed to investigate the relationship between dietary patterns and NR3C1 gene methylation in users of the Brazilian Public Unified Health System (SUS). Methods: We recruited 250 adult volunteers and evaluated their socioeconomic status, psychosocial characteristics, lifestyle and anthropometry. Peripheral blood was collected and evaluated cortisol levels, glycemia, lipidogram and insulin resistance, and methylation of CpGs 40 to 47 of 1F region of the NR3C1 gene. Factors associated with methylation levels were evaluated using generalized linear models (p<0.05). Lifestyle variables and health variables were used as confounding factors. Results: Our cross-sectional study obtained an association between NR3C1 DNA methylation measured and intake of processed foods. We also found a relevant association between NR3C1 DNA methylation in the average of the segment analyzed, components 1 and 2 (40-43 and 44-47, respectively) and industrialized products consumption pattern in relation to BMI, serum cortisol levels and lipid profile. These results may indicate a relationship between methylation and metabolic changes related to the stress response. Conclusion: These findings suggest association between methylation and metabolic alterations with stress response. In addition, the present study highlights the significant role of diet quality as a stressinducing factor that influences NR3C1 methylation. This relationship is further linked to changes in psychosocial factors, lifestyle choices, and cardiometabolic variables including glucose levels, insulin resistance and hyperlipidemia. 9 Variable Aderence healthy pattern pvalue Aderence Industrialized pattern pvalue Aderence mixed pattern pvalue Total No Yes No Yes No Yes Socioeconomic Gender n (%)